Green Hydrogen and the Energy Transition: Hopes, Challenges, and Realistic Opportunities - Alessandro Franco (Hydrogen)
This paper provides a system-level and dimensional analysis of green hydrogen, assessing its realistic deployment potential within broader energy transitions. While green hydrogen—produced via electrolysis using renewable electricity—is often promoted as a versatile decarbonization solution for industry, mobility, and civil applications, its practical implementation is constrained by high energy consumption, conversion inefficiencies, and complex supply chain requirements. This study highlights typical energy demands across key sectors and evaluates the scale of the renewable infrastructure needed to support them, offering quantitative insight into the feasibility of large-scale hydrogen integration. It also reflects current technological maturity, noting that many promising solutions remain far from industrial readiness. Finally, the paper underscores the importance of targeted policies and bankable investment models to foster the development of hydrogen ecosystems, emphasizing that its role should be framed within a selective, evidence-based strategy that focuses on high-impact applications. The analysis identifies key dimensional challenges, including the magnitude of renewable energy capacities required for sector-wide hydrogen integration and the scale of infrastructure investments needed to bridge current gaps.